1976
DOI: 10.1136/ard.35.5.446
|View full text |Cite
|
Sign up to set email alerts
|

Demonstration of antibodies to collagen and of collagen-anticollagen immune complexes in rheumatoid arthritis synovial fluids

Abstract: Annals of the Rheumatic Diseases, 35, 446-450. Demonstration of antibodies to collagen and of collagen-anticollagen immune complexes in rheumatoid arthritis synovial fluids. Twenty-nine synovial fluids from patients with rheumatoid arthritis (RA) and 10 synovial fluids from patients with other joint diseases were investigated with regard to the presence of antibodies to denatured human collagen and of collagen-anticollagen immune complexes. 12 of the 29 RA synovial fluids showed anticollagen titres from 1: 16 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
18
0

Year Published

1978
1978
2008
2008

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 58 publications
(19 citation statements)
references
References 5 publications
1
18
0
Order By: Relevance
“…Several investigators have found antibodies in the sera and synovial fluid of patients with rheumatoid arthritis (RA) and have hypothesized that collagen autoimmunity may be responsible, at least in part, for the observed pathology (16)(17)(18). Antibodies reactive with both native and denatured types I, 11, and I11 collagen have been described in rheumatoid arthritis but the greatest reactivity was found against denatured collagen (19,20).…”
Section: Discussionmentioning
confidence: 99%
“…Several investigators have found antibodies in the sera and synovial fluid of patients with rheumatoid arthritis (RA) and have hypothesized that collagen autoimmunity may be responsible, at least in part, for the observed pathology (16)(17)(18). Antibodies reactive with both native and denatured types I, 11, and I11 collagen have been described in rheumatoid arthritis but the greatest reactivity was found against denatured collagen (19,20).…”
Section: Discussionmentioning
confidence: 99%
“…These antibodies engage in the formation of complement-binding antigen-antibody complexes which are said to play a major part in the induction and perpetuation of synovial inflammation. In the SF of human patients with RA and OA, anticollagen antibodies (Menzel et al, 1976(Menzel et al, , 1978Stuart et al, 1983;Jasin, 1985) and immune complexes (Cooke, 1980) have been discovered. In RA, these antibodies are produced locally by plasma cells that are located in the synovial tissue (Smiley et al, 1968).…”
Section: Humoral Immunity In Cruciate Diseasementioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9][10][11][12][13][14][15] Among these antibodies, the rheumatoid factor (RF), mainly of the M isotype, is considered to be characteristic of the disease. Thus it is currently used in the diagnosis of RA' "' and constitutes one of the classification criteria proposed by the American Rheumatism Association.…”
Section: Introductionmentioning
confidence: 99%
“…The serum samples are classified according to the increasing immunoreactivity to the B protein. Among the 15 RA serum samples, only one reacts with the B protein alone (1), two of them are positive with only the A and B proteins(2,4) whereas the others react with the three proteins A, B and C(3,(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15). The serum samples with high titre-like values of 'AKA react with the three proteins according to a continuous pattern which extendsfrom the A to the C protein…”
mentioning
confidence: 99%